RANCANG BANGUN SMART CHARGING CONTROLLER PADA PROTOTIPE MOBIL LISTRIK BERBASIS ARDUINO MEGA 2560 - Tomi Darmanto Manik (2024)
This research based on the problem of air pollution in Jakarta, documented as the world's worst in 2023. The Indonesian government's response involves promoting electric vehicles, aiming to combat the transportation sector's 44% contribution to air pollution. Despite these efforts, obstacles like lengthy battery charging times and a scarcity of charging stations hinder public interest. The study focuses on designing a hybrid charging control device for a solar-equipped prototype electric vehicle. Utilizing a quantitative experimental approach, the research implements a smart charging controller with a 12V adapter and a 10 WP solar panel. Test results reveal the Arduino Mega 2560-based controller enhances efficiency by supplying power below 13V and disconnecting at 13.4V. Conclusively, the device extends a 5Ah battery's consumption time by 1 hour, showcasing the significant potential of the Arduino Mega 2560-based smart charging controller in enhancing charging efficiency and ensuring future transportation sustainability.